A Study on Ethnomedicinal plants used to cure Respiratory Disorders in Top Northern Himalayan Regions of India - RAZIA PARVEEN; SABINA BASHIR (The Bioscan, 2024)
The present paper compiled and analyzed traditional ethnomedicinal knowledge used to treat various respiratory disorder by different communities of three northern most regions of India. Ethnobotanical studies carried out were searched from books, journals, from scientific databases like JSTOR, Scifinder, Scopus, Science direct, google scholar, Pub med and web of science. A total of 178 plant species belonging to the 138 genera of 51 families were found to be used by different communities to treat respiratory disorders. Some of the mostly used plant species include Aconitum Heterophyllum, Ephedra gerardiana, Inula racemosa and Ocimum sanctum. The maximum plant species used in the study area belonged to Asteraceae (28 species), followed by Lamiaceae (15 species) and so on. Mostly the plant parts like leaves, root, stem, flower fruit and whole plant were found to treat Asthma, Bronchitis, Cough etc. In addition, scientific research is needed to validate the usage of these medicinal plants and to prove the claimed Ethnobotanical activity of these medicinal plants.